Analiza mowy jako narzędzie diagnozy chorób neurodegeneracyjnych - Jankowska , Karolina (Investigationes Linguisticae, 2022)
Objective: The aim of the work is to compare the results of research on the oral language of people with neurodegenerative diseases. On the basis of literature, research results and available information, research methodologies in the subject and test results are presented. Speech variables that have been considered in the studies were presented, including linguistic, phonetic and phonological features, prosodic, acoustic, lexical, semantic, syntactic and morpho-syntactic features. Material and methods: A comprehensive review and analysis of literature, articles in peer-reviewed journals, in the field of language disorders resulting from brain damage resulting from neurodegenerative diseases. Conclusions: Studies show that the speech analysis is a crucial diagnosis tool, which can be used for early neurodegenerative changes recognition. No such studies have been carried out in the Polish language so far.